Number of children or family size? : An examination of the influence of parenthood on well-being among the Igbo of Eastern Nigeria - Agbo, Aaron A.; Onyishi, Amuche (Journal of Psychology and Allied Disciplines, 2023)
The presence of African samples in the bourgeoning research on the impact of parenthood on wellbeing is only beginning to emerge. In the present study, and anchoring on existing literature, we investigated the interactive role of the number of children, family size, economic status, and love of the family on the wellbeing of Nigerian parents. Economic status, family size, and love of family interactively played significant roles in parents’ well-being. Parents on the bottom of the economic ladder, engaged in junior job positions, and had larger family size experienced poorer life satisfaction. However, love of family potentiated parents’ experiences of life satisfaction, and equally reduced the negative impact of family size on parents’ life satisfaction. The result of the study shows that a robust and nuanced understanding of the effect of parenthood on well-being requires an approach that takes into consideration the social, economic, and psychological circumstances surrounding the families.